Phase-dependent transparency in a two-level system with applications to all-optical switching - Ramaswamy, Aneesh; Malinovskaya, Svetlana A. (Frontiers in Quantum Science and Technology, 2025)
The phenomenon of transparency, conventionally studied in three and higher level atomic systems, is extended to the case of a two-level system (TLS), where we use a semiclassical framework to describe the transparent propagation of classical fields in a medium of TLS scatterers. We demonstrate a new form of transparency with fast pulses, accounting for the initial state of the TLS, which we call phase-dependent transparency. Using the phenomenon of photon locking, we showed that TLSs initialized in maximum coherence states exhibit transparency to resonant fields when there is phase-matching between the phase of the atomic coherence and that of the probe field. An application to the problem of all-optical switching is also discussed, where on-demand transmission is generated by controlling the relative phase between a π/2 pump pulse and the transmitted probe pulse.